Examining the role of adverse childhood experiences in its association with vindictiveness, emotional awareness, hurt feelings, and self-esteem - Shazia Khalid; Sumaya Batool; Sabir Zaman (Discover Psychology, 2024)
Abstract Background Adverse childhood experiences (ACEs) play a significant role on emotional and psychological outcomes in adulthood, including vindictiveness, emotional awareness, self-esteem and hurt feeling. This study sought to examine the relationship between early ACEs and their effects on vindictive behavior, emotional awareness, hurt feelings, and self-esteem in adults. Method A total of 500 university students aged 18 to 47 participated in the study, among these 246 were selected through screening. Initially adverse childhood experiences of participants were screened using a Life Event Scale. Vindictive behavior was assessed using the Vengeance Scale, while Emotional awareness, hurt feelings, and self-esteem were measured through the Trait Emotional Awareness Scale, Hurt Feeling Scale, and Self-Esteem Scale, respectively. Results The findings suggests that individuals who recalled negative childhood experiences were more likely to show vindictive behavior in adulthood. Moreover, the study revealed that this relationship between adverse childhood experiences and vindictive behavior were higher in individuals with low emotional awareness and self-esteem. Furthermore this association become significantly stronger in individuals experiencing heightened level of hurt feelings. Conclusion The study highlights the significance of early adverse childhood experiences in understanding of vindictive behavior. Furthermore, it emphasizes that low emotional awareness, self-esteem, and the experience of hurt feelings act as mediating factors associated with behavioral patterns.